KAJIAN TENTANG PEMASARAN ONLINE UNTUK MENINGKATKAN PELUANG BISNIS - Farika Nikmah (Adbis: Jurnal Administrasi dan Bisnis, 2017)
The main objective is to promote the brand, build preference and increase sales through various digital marketing techniques. The digital era goes hand in hand with technological developments, resulting in more choice in selecting marketing channels. This research is a survey research, with the guest speaker is a student Department of Business Administration Politeknik Negeri Malang who have independent creative business based online using social media. Th with some company names. Like IceAh, Sabilahijab, Bakso Bakar Mami, Gedang Gantheng, and many more. This study provides an overview of what is the basis of media selection, strategy, segment selection, strengths and weaknesses, and what failure has been experienced in running a business. The desired hope of this research is to become a reference for prospective actors, especially young people in online marketing. So that the future can take a good example and complete it into a more powerful strategy.